rozwiąż równanie
a)11×a-6=7×a-4
b) 4×a+3=9×a-12
plis pomocy ​


Odpowiedź :

Odpowiedź:

Szczegółowe wyjaśnienie:

11a -6=7a -4

4a =2. /4

a =1/2

4a+3=9a -12

-5a= - 15 /(-5)

a=3

Odpowiedź:

a)  11 *a -6 = 7*a-4

     11a -6= 7a-4

   11a- 7 a= -4 +6

        4a= 2 /:4

       a= 2/4= 1/2

spr..    11*1/2 -6 = 7*1/2 -4

             11/2-6= 7/2-4

             5 i 1/2 -6= 3 i 1/2-4

                   -1/2= - 1/2

                   L=P

b)   4*a +3 =9*a -12

            4a+3= 9a-12

          4a-9a= -12 -3

          -5a = -15 /*(-1)

           5a= 15 /:5

          a=3

spr..   4*3 +3= 9*3-12

               12+3= 27-12

                   15=15

                      L=P

Szczegółowe wyjaśnienie:

 * ten znak oznacza mnożenie